2017
DOI: 10.1093/jhered/esx001
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Linkage of Molecular Markers with Sex Determination Gene in Pacific Salmon (Oncorhynchus spp.)

Abstract: In the present study, we tested the congruence between the sdY sex-specific marker and other commonly used male markers, located on the Y-chromosome, with the sex phenotypes in 5 species of Pacific salmon in Asian waters, including Chinook, chum, sockeye, masu, and pink salmon. We found that the localization of the sex-specific marker of both males and females of these species is not consistent with the phenotypic sex. Also, no linkage was found between noncoding markers and the sdY gene in the same species sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Male kokanee from the upper Columbia River drainage were sdY-negative (personal communication DS and RHD), which is consistent with the resequencing data aligned to the sdY sequence. It is also congruous with a previous study finding a high percentage of sdY-negative sockeye salmon males (~30%) in an upper Columbia River hatchery [ 27 ], and another study with similar findings in samples collected from Asian populations [ 147 ]. Atlantic salmon females have been identified with sdY, but likely have autosomal pseudocopies rather than a bonafide function sex-determining copy (bioRχiv [ 148 ]) [ 33 ].…”
Section: Discussionsupporting
confidence: 82%
“…Male kokanee from the upper Columbia River drainage were sdY-negative (personal communication DS and RHD), which is consistent with the resequencing data aligned to the sdY sequence. It is also congruous with a previous study finding a high percentage of sdY-negative sockeye salmon males (~30%) in an upper Columbia River hatchery [ 27 ], and another study with similar findings in samples collected from Asian populations [ 147 ]. Atlantic salmon females have been identified with sdY, but likely have autosomal pseudocopies rather than a bonafide function sex-determining copy (bioRχiv [ 148 ]) [ 33 ].…”
Section: Discussionsupporting
confidence: 82%
“…Members of the Coregoninae subfamily lack sdY male specificity and the existence of sex specific inactive copies in females has been invoked to explain this phenomenon ( Yano et al, 2012 ). Together with the mobile nature of the sdY gene, the loss of function may also explain the existence of inactive sdY copies in other salmonid species ( Podlesnykh et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, assays have been used to determine genetic sex in adults that were not phenotyped but subsequently used for sex-specific studies such as investigation into the genetic basis of age at maturity ( Ayllon et al, 2015 ; Barson et al, 2015 ; Kusche et al, 2017 ; Ayllon et al, 2019 ). However, several studies have reported a discordance between phenotypic and sdY sex within the Salmonidae family ( Eisbrenner et al, 2014 ; Cavileer et al, 2015 ; Larson et al, 2016 ; Podlesnykh et al, 2017 ). Discordance between DNA markers for sex and phenotypic sex is not uncommon in fishes, and it is typical in a species displaying a combination of genetic and environmental sex determination ( Hattori et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported a discordance between phenotypic and sdY sex within the Salmonidae family (Eisbrenner et al 2014;Cavileer et al 2015;Larson et al 2016;Podlesnykh, Brykov, and Kukhlevsky 2017). Discordance between genetic and phenotypic sex is not uncommon in fishes, and it is typical in a species displaying a combination of genetic and environmental sex determination (Hattori et al 2019).…”
Section: Introductionmentioning
confidence: 99%